ANALISIS EFEKTIVITAS, EFISIENSI, DAN KONTRIBUSI RETRIBUSI PARIWISATA SEBAGAI SUMBER PENERIMAAN PENDAPATAN ASLI DAERAH KABUPATEN WONOGIRI TAHUN 2013 – 2017 (Studi Kasus pada Objek Wisata Waduk Gajah Mungkur Wonogiri) - Handika Rizka Ari Wibowo; Suharno Suharno; Djoko Kristianto (Universitas Slamet Riyadi, 2020)
The purpose of this study is to analyze the effectiveness, efficiency and contribution of tourism retribution as a source of revenue for Wonogiri District's original revenue in 2013 - 2017 case studies on Gajah Mungkur Reservoir Wonogiri tourism object. This research is a case study conducted in Wonogiri Regency in 2013 - 2017. Secondary data used in this study came from the Dispora of Wonogiri Regency, with research objects on the Gajah Mungkur Wonogiri Reservoir. The analysis technique used is the analysis of effectiveness, efficiency and contribution. The results of the effectiveness analysis show that the receipt of tourism retribution in the Gajah Mungkur Wonogiri Reservoir in 2013 - 2017 is said to be very effective because the percentage of effectiveness is 102,77% so it is more than 100%. These results indicate the realization of tourism retribution receipts in the Gajah Mungkur Wonogiri Reservoir can meet the targets set by the Wonogiri District Government. Efficiency analysis shows that the receipt of tourism levies in Gajah Mungkur Wonogiri Reservoir in 2013 - 2017 is said to be efficient because the percentage is 19,25% which is located between 10% - 20%. This result shows that the average realization of tourism retribution in the Gajah Mungkur Reservoir can be used to cover the costs incurred for operational retribution by the UPTD Gajah Mungkur Wonogiri reservoir. While the contribution analysis shows the contribution of tourism retribution in the Gajah Mungkur Wonogiri reservoir in 2013 - 2017 is said to be very lacking because the percentage is 1,51% which is located between under 10%. The contribution of retribution from the tourism sector of the attraction of Gajah Mungkur Wonogiri Reservoir as a source of revenue for PAD is still small.